Kognitive Neurophysiologie des Menschen - Human cognitive neurophysiology Vol. 6 (2013) - (:unkn) unknown; Justus Liebig University Giessen (My University, 2013)
B. Kopp & T. Fingscheidt: Electrophysiological Correlates of Orientation Asymmetry. Abstracts of the 21st German EEG/EP Mapping Meeting. Announcements - Ankündigungen.
Keywords: ddc:610